Journal of Business Valuation and Economic Loss Analysis (De Gruyter, 2006)
The Journal of Business Valuation and Economic Loss Analysis (JBVELA) is a refereed academic journal with the mission to improve the practice of business valuation, economic loss analysis, and risk management by helping to inform academics, practitioners and attorneys about theoretical and practical developments in these fields.